IMPACT OF AGRICULTURE ON ENVIRONMENT AND BIOREMEDIATION TECHNIQUES FOR IMPROVISATION OF CONTAMINATED SITE (International Association of Biologicals and Computational Digest, 2022)
Sustainable development requires the progress and preferment of environmental management and a persistent exploration and improvement for green technologies to treat a wide range of habitats contaminated by disorganized anthropogenic activities. Bioremediation is an excellent and effective cleaning technique to remove toxic waste from contaminated environment. Bioremediation is vastly involved in degradation, eradication, immobilization, or detoxification of diverse chemical wastes and physical hazardous materials from the surrounding through the all-embracing with the help of microorganisms and plants. Bioremediation technique is widely used to treat wastewater and to remove agricultural chemicals (pesticides and fertilizers) that leach from soil into groundwater. Certain toxic metals, such as mercury, selenium and arsenic compounds, can also be removed from water by bioremediation. Thus, bioremediation is a research and solution oriented technology that needs a prior thorough understanding of different types of available processes for improvisation and clean-up of contaminated sites. In this review, impact agricultural pollution, principle of bioremediation process and, different types of in-situ and ex-situ bioremediation techniques have been discussed.
Keywords: Agriculture, bioremediation, in-situ, ex-situ, phytoremediation